Softwood Distillate as a Bio-Based Additive in Wood-Plastic Composites. (3rd July 2016) - Väisänen, Taneli; Heikkinen, Jorma; Tomppo, Laura; Lappalainen, Reijo
Abstract : The possibility of using softwood distillate as a bio-based additive or filler in wood-plastic composites (WPCs) was studied by adding various amounts (1–20 wt%) of distillate to a commercial WPC consisting of thermally treated sawdust in a polypropylene (PP) matrix. Softwood distillate was obtained as a secondary product from industrial ThermoWood® processing and it was further processed in the laboratory. The addition of softwood distillate significantly enhanced the mechanical properties of WPC when the distillate content was 2 wt%; tensile strength increased by 5%, tensile modulus by 3%, flexural strength by 3%, and modulus of elasticity by almost 2% compared with the unmodified WPC. In addition, a considerable decrease (over 16%) in water absorption was observed on distillate addition. Proton-transfer-reaction time-of-flight mass-spectrometry (PTR-TOF-MS) analyses revealed that the addition of softwood distillate increased release rates of volatile organic compounds (VOCs) in general, and that the odor of acetaldehyde and guaiacol is detectable in several WPCs. Overall, softwood distillate had positive effects on this particular WPC.